The impact of information and communication technologies on informal scientific communication: A naturalistic inquiry approach. Issue 6 (7th September 2015) - Shehata, Ahmed Maher khafaga; Ellis, David; Foster, Allen
Abstract : Purpose: – This study aims to accomplish three objectives: first, to investigate the role and impact of information and communication technologies on the practice of science in the UK; second, to examine and characterise changes in scholarly communication activities such as information seeking, publishing and collaboration; and third, to investigate the validity of the current scholarly communication models and to determine whether there is a need for a new model. Design/methodology/approach: – The study deployed a naturalistic inquiry approach using semi-structured interviews as a qualitative research tool. A theoretical sample of 40 researchers in four universities were interviewed to gather data regarding informal scholarly communication practices, factors that affect the researchers' decisions and changes in the scholarly communication system. Findings: – The results of the interviews suggest that there are three types of scholars who engage in scholarly communication activities. First, the "orthodox scholar", who only uses formal and traditional scholarly communication approaches. Second, the "moderate scholar", who prioritises formal communication approaches but, at the same time, is trying to get benefits from informal channels. Finally, the "heterodox scholar", who uses all channels available in scholarly communication. The study also proposes a model of scholarly communication that reflects the current changes in scholarly research. Research limitations/implications: – The paper describes the changes in informal scholarly communication practices in four universities in the UK. However, because the study used a naturalistic inquiry approach, the results cannot be generalised to a different population. Originality/value: – There is limited literature investigating the changes in informal scholarly communication practices. The value of the current study lies in being the first study in this area that uses a naturalistic inquiry approach to investigate the changes in informal scholarly communication practices, and to develop a new model of scholarly communication.